Movilidad y expansión en la construcción política de los Estados Unidos: «estos errantes colonos» en las fronteras españolas del Misisipí (1776-1803) - Hilton, Sylvia L. (Revista Complutense de Historia de América, 2002)
The United States has often been perceived as a mobile society. The analysis of Spanish sources during its early formative period reveals that this characterization was closely linked by Spanish observers to diverse aspects of the ideological and political construction of the nation. Their views contribute new perspectives on the historiographical debates concerning demographic trends, the relationship between territorial expansion and collective identity, the protagonism of pioneering settlers measured against the more diluted role of government leadership, western separatism, and the displacement of native American peoples.
Keywords: United States; Spain; Mississippi; frontiers; settlers; mobility; expansion; national construction; 1776-1803